Teks Mitos Dewa Nini di Desa Pakraman Rianggede Tabanan: Analisis Struktur dan Fungsi - Anggitha Pradnya Wulandari, Putu; Ngurah Sulibra, I Ketut; Duana Sutika, I Nyoman (Humanis; Vol 21 No 1 (2017)DO - 10.24843/JH.2017.v21.i01.p14, 2017)
The study is titled, "The Mythical Text of the God of Nini in the Pekraman Rianggede Village, Tabanan Regency: Structural Analysis and Function". This study uses structural theory and function theory. This study aims to describe the narrative structure of the mythical texts of the God of Nini in the village of Pekraman Rianggede and to analyze the functions contained in the mythical texts of the God. The stage of provision of data used by the method of observation with interview techniques assisted with recording techniques and note techniques to take a note and record the important things delivered by the speakers. Then in the stage of data analysis used qualitative methods. In this stage is also supported by analytical descriptive method and assisted with translation techniques. At the presentation stage of the data analysis, the method used is the informal method and assisted with deduktif  techniques. Narrative structures that build the mythical texts of God Nini ie plot, figure, theme and background. In this myth there is a ritual structure, the ceremony ngiring God Nini and ceremony nunas pica. The functions contained in the myth of the God Nini, is (1) ritual function, (2) the social function and (3) the function of customs.